2010
DOI: 10.15193/zntj/2010/71/122-131
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Microbiological Contami Nation of Fresh Basil and Mint

Abstract: Celem badań było określenie stanu mikrobiologicznego różnych odmian bazylii i gatunków mięty, bezpośrednio po zbiorze roślin. Badaniami objęto cztery odmiany bazylii pospolitej (Ocimum basilicum): 'Fine Verde', 'Genovese', 'Red Rubin' i 'Wala' oraz ziele mięty: pieprzowej białej (Mentha x piperita f. pallescens), cytrynowej (Mentha x piperita var. citrata), kędzierzawej (Mentha crispa) i nadwodnej (Mentha aquatica). Ocenie poddano ulistnione, niemyte pędy ziół, które zbierano w fazie tuż przed kwitnieniem. Stw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Considering these requirements, moulds contamination of the tested edible flowers, ranging from 2.3 to 4.95 CFU/g, can be considered moderate, while yeast contamination (from 2.3 to slightly more than 6 CFU/g) -too high. The occurrence of yeasts and moulds at similar levels was found by researchers evaluating the microbiological quality of ready-to-eat salads and selected herbs (Adeyemi et al, 2019;Mohammad et al, 2012;Wójcik-Stopczyńska et al, 2010).…”
Section: Resultssupporting
confidence: 63%
“…Considering these requirements, moulds contamination of the tested edible flowers, ranging from 2.3 to 4.95 CFU/g, can be considered moderate, while yeast contamination (from 2.3 to slightly more than 6 CFU/g) -too high. The occurrence of yeasts and moulds at similar levels was found by researchers evaluating the microbiological quality of ready-to-eat salads and selected herbs (Adeyemi et al, 2019;Mohammad et al, 2012;Wójcik-Stopczyńska et al, 2010).…”
Section: Resultssupporting
confidence: 63%
“…Especially, essential oils and hydrosols are being as a promising source of natural active compounds that protect plant crops and manage pest infestations in cultures. Recently, some essential oils and hydrosols were used as natural agents to fight fungi and to prevent the deterioration of food products in the postharvest phase …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it has been shown that Salmonella and E. coli 0157:H7 can survive or grow in acidic produce, such as apples and tomatoes (3,15). Basil is characterized by the presence of high numbers of background microbiota and contains essential oils with an antibacterial activity (16,57,59). Indigenous microbiota may compete with pathogens for physical space and specific nutrients or produce antagonistic compounds that negatively affect the viability of the pathogens on fresh produce (19,41).…”
mentioning
confidence: 99%